El mal tiene motivos que la razón desconoce: la narrativa policial de Carlos Tromben - Poblete Alday, Patricia (Anales de Literatura Hispanoamericana, 2008)
Criminality written on Carlos Tromben’s novels goes beyond “institucionality/public” and “private/passion” areas to come back to the basis of the policial style, using elements of the mistery novel and gothic terror. This not only questions the rationality as the way to take us to the truth and to reestablish the order after the crime, but also allows a reflexion about the atavic relationship between evil, esoterism and aesthetic.